Considerations on the Management of Zinc Phosphide Toxicity and Proposed Therapeutic Approaches - Sayed Mahdi Marashi; Foroozan Faress; Kurosh Jodaki; Leyla Abdolkarimi; Zeynab Nasri Nasrabadi (Journal of Nepal Medical Association)
Zinc phosphide (ZnP) is a rodenticide commonly used in agriculture for pest control, but it can causeacute human poisoning, through ingestion in suicide attempts. The toxicokinetics of ZnP are not well understood, although it is believed that its primary mechanism of toxicity involves the inhibition of Complex IV of Cytochrome C Oxidase, similar to aluminum phosphide (ALP) poisoning. However, there are notable differences between the two. The rarity of acute ZnP toxicity and the misconception that it mirrors ALP poisoning have hindered the development of effective treatment strategies. This review critically examines the challenges of existing treatment protocols and proposes new approaches based on current evidence. A thorough literature review on the management of ZnP and ALP poisoning was conducted. Due to the delayed onset of symptoms in ZnP poisoning, aggressive gastrointestinal decontamination is recommended prior to toxin absorption. Furthermore, the potential for acute liver failure in early ZnP cases requires targeted treatment for hepatic injury. Since systemic absorption of phosphine can produce effects similar to ALP poisoning, existing ALP treatment protocols may also aid in managing ZnP toxicity. This study proposes a treatment protocol for ZnP poisoning, emphasizing the need for further randomized trials to validate its effectiveness.